Logistics-related risk management in a global supply chain - Focus on the container liner shipping - Kyllönen, Alina (My University, 2022)
This research discusses the logistics-related risk management in a manufacturing company, focusing on the recent disruptions in maritime shipping, such as Covid-19 pandemic and its ripple effects in container liner shipping. The object of this research is to provide tools to improve the risk identification and assessment in the case company and to provide a review to the case company of its current logistics-related risk management. The theoretical framework of this research was built through discussing global supply chain risks, the three-step supply chain risk management process, and especially mitigation strategies. The container liner shipping and its recent disruptions, such as port congestion and container shortage, are discussed as well. The research was conducted as qualitative research and the data was collected through total of six semi-structured interviews, of which five were held inside the case company’s different organizations and one in the primary freight forwarder’s company. The interviewees were selected due to their central and critical role in material purchasing and risk management. According to the results, the logistics-related risk management has been successful during the recent logistical disruptions. The case company has successfully managed to protect its production continuity through several mitigation strategies, such as control, cooperation, and flexibility, and even surpassed its financial objectives in 2021. However, as the results show, the case company has had difficulties regarding the implementation of strategic decisions, as the company has had rather weak supplier contracts and the company lacks alternative suppliers with certain strategic components. Furthermore, as an interesting result, the interviewees have different approaches to risk management regarding their position and experience, and the results show that the operational level has little visibility to proactive risk identification and to strategic risk management and decision-making. According to the results, the risk management is well implemented amongst the strategic level, but the operational level has as critical role in the risk identification and assessment.

Tässä tutkimuksessa tarkastellaan logistista riskinhallintaa valmistavassa case-yrityksessä, keskittyen etenkin viimeaikaisiin meriliikenteen häiriötilanteisiin, kuten Covid-19 pandemiaan ja sen heijastinvaikutuksiin konttilinjaliikenteessä. Tutkimuksen tarkoituksena on tarjota case-yritykselle keinoja parantaa sen riskien tunnistamista ja arviointia, sekä tarjota yritykselle tilannekatsaus sen logistisesta riskinhallinnasta. Tutkimuksen viitekehitys rakennettiin tarkastelemalla globaaleja toimitusketjujen riskejä, 3-vaiheista toimitusketjujen riskinhallintaprosessia, ja etenkin riskien lieventämisstrategioita. Tutkimuksessa käsiteltiin myös konttilinjaliikennettä sekä sen viimeaikaisia epävarmuuksia, kuten satamaruuhkaa ja konttipulaa. Tutkimus toteutettiin kvalitatiivisena tutkimuksena, ja aineisto kerättiin yhteensä kuudella puolistrukturoidulla haastattelulla, joista viisi pidettiin case-yrityksen sisällä eri organisaatioissa sekä yksi case-yrityksen päähuolitsijayrityksessä. Haastateltavat valittiin tutkimukseen, sillä heillä on oleellinen ja kriittinen tehtävä yrityksen materiaalinhankinnassa sekä riskinhallinnassa.Tulokset osoittavat, että case-yrityksen riskinhallinta on ollut onnistunutta viimeaikaisten logististen häiriöiden aikana. Yritys on onnistunut suojaamaan tuotantonsa jatkuvuutta useilla eri lieventämisstrategioilla, kuten kontrollilla, yhteistyöllä sekä joustavuudella, ja onnistunut jopa ylittämään taloudelliset tavoitteensa vuonna 2021. Tulokset kuitenkin osoittavat, että case-yrityksellä on ollut haasteita strategisten päätösten implementoinnissa, sillä yrityksellä on ollut käytössä heikot toimittajasopimukset sekä yritykseltä puuttuu edelleen vaihtoehtoiset toimittajat tiettyjen strategisten komponenttien osalta. Tämän lisäksi tulokset osoittavat mielenkiintoisen havainnon siitä, että riskinhallinta on vahvasti sidoksissa haastateltavan työtehtävään ja kokemukseen. Tulokset osoittavat, että operatiivisella tasolla on vähän näkyvyyttä proaktiiviseen riskien tunnistamiseen sekä yrityksen strategiseen riskinhallintaan ja päätöksentekoon. Tulosten perusteella riskinhallinta on hyvin jalkautunut strategisella tasolla, mutta operatiivisella tasolla on yhtä kriittinen rooli riskien tunnistamisessa ja arvioinnissa.
Keywords: global supply chain, supply chain risk management, supply chain risk management process, mitigation strategy, container liner shipping, Covid-19, container shortage globaali toimitusketju, toimitusketjujen riskinhallinta, toimitusketjujen riskinhallintaprosessi, lieventämisstrategiat, konttilinjaliikenne, Covid-19, konttipula